ANALISIS PELAYANAN RUMAH SAKIT TERHADAP KEPUASAN PENGGUNA JAMINAN KESEHATAN ACEH (JKA) DI BANDA ACEH - T. Alamsyah T. Alamsyah (Prosiding Seminar Nasional USM, 2019)
Assessed the quality of a good Health care if Health care is organized can make you Bee satisfied on every patient. Hospital as one of the subsystems provide two types of Health care services to the Community of Health services and administrative services. One public Health care programs in the province of Aceh Government is Aceh’s Health Insurance program . Some complaints  participants who have received services from the hospital staf is the lack of service and attention to participants HIA, Maintenance procedures, the appointment of the rol where less attention was impressed hospitalization services, use of facilities associated with the is complicated by reason of being damaged, service to patients HIA impressed secondary compared to patients with non-JKA and waiting time in the process of taking a drug that is too long. This Research aims to ditermine and analyze hospital services on user statisfaction Aceh Health Insurance  in Banda Aceh  2011. This descriptive analytic study desing, the Research sample was  patient or family who underwent inpatient services for 2 days or more as many as 185 patients. Data analysis included analysis of simple linear regression (CI = 95%, analysis of variance (ANOVA) (CI=95%) and multiple linear regression statistical tests. The results obtained by statistical analysis that Three was a significant effect of administrative services (p=0,0080,05), no significant effect paramedical care (p=0,0000,05), Three is a significant influence) supporting service medic (p=0,0060,05, Three was no significant difference between the service on the RSU RSUZA Meuraxa (p= 0,709), between services on RSUZA with RSIA (p=0,110), and between the RSU Meuraxa with RSIA(p=0,189). It is recommended for hospitals should retain or even improve the quality of Health services, both in terms of facilities, medical services and administrative services.